Attractors for the Long-short Wave Equations (Journal of Partial Differential Equations, 2020)
In the present paper, we study the long time behaviour of solutions for the long-short wave equations with zero order dissipation. We first construct the global weak attractor for this system in H²_{per} × H¹_{per}. And then by exact analysis of two energy equations, we show that the global weak at attractor is actually the global strong attractor in H²_{per}.
Keywords: Global attractor; zero order dissipation; long-short wave equations